Solar Cells: Synthesis of Organic–Inorganic Lead Halide Perovskite Nanoplatelets: Towards High‐Performance Perovskite Solar Cells and Optoelectronic Devices (Advanced Optical Materials 9/2014). Issue 9 (September 2014) - Ha, Son Tung; Liu, Xinfeng; Zhang, Qing; Giovanni, David; Sum, Tze Chien; Xiong, Qihua
<x xml:space="preserve">Abstract</x> Highly crystalline organic‐inorganic lead halide perovskite nanoplatelets are grown on muscovite mica by Q. H. Xiong and co‐workers utilizing van der Waals epitaxial growth followed by thermally intercalating methyl ammonium halides. On page 838, the resultant CH3NH3PbI3 platelets show excellent optical properties with an electron diffusion length of more than 200 nm, which is approximately twice that of the solution‐processed films, suggesting considerable promise for photovoltaics and opto‐electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>